Całkowe Kryterium Oceny Dynamiczności Obiektów Mechanicznych - Cempel, C. (Engineering Transactions, 1973)
In this paper is proposed a new integral criterion of dynamics of mechanical objects, called the "mobility criterion". It is shown that mobility may be determined experimentally by means of excitation processes with a limited frequency band, in the simplest case consisting of a series of two-sided impacts.